Perbaikan Postur Kerja Operator Pengelasan dengan Metode Quick Exposure Check (QEC) - Eka Indah Yuslistyari; Aden Adhadin (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2018)
CV. Surya Teknik Mandiri is a company engaged in lathe and welding services located in Serang-Banten. Work is usually done such as screw making and welding of axle cages, where products are made according to customer orders. This study focused on one part of the work that has the highest level of fatigue through a fatigue questionnaire caused by squat work postures, namely the welding section involving two operators. This study aims to determine the measurement value of the exposure score, exposure level and to reduce MSDs complaints with the design of repair tools for welding operators in this study using the Quick Exposure Check (QEC) research method by distributing observer questionnaires and operators, and using the Anthropometry approach in measuring design tools for improving operator work posture. Based on the results of research on welding operators 1, the total exposure score was 106 with an exposure level of 59.55%. While for operator 2, there is a total exposure score of 124 and an exposure level of 69.66%. An action level for both operators needs further research and changes. Next, repairs are made to reduce the exposure level value in the welding work. Repairs are made with the aim of making the condition safe, comfortable and do not cause complaints MSDs when working, namely at the workstation standing by designing a tool in the form of a welding work desk. After implementing the welding workbench for the two operators and recalculating the QEC value, the operator one exposure level of 48.31% and for operator 2 49.43% with action levels need further research.